The Beginning and Evolution of the Progressive Movement in Saraiki Language - Perveen, Fauzia; Arif, Muhammad; Saleem, Muhammad (sourcecoder, 2024)
The Saraiki language is the language of the central region of the Indus valley. On one hand it is the sister of Sindhi language and on the other hand it is related to Punjabi language and the interesting thing is the same language is spoken and understands in all four provinces of Pakistan. When we search for the effects of the progressive movement in the Saraiki language and literature, its impact of the establishment of Pakistan become more apparent like other regional languages, poetry hold significant in Saraiki literature. Over time, the poets and writers from the Saraiki region have adapted to the changing of time, they changed their thoughts and ideas, the impact of which are seen in their poetry. This article discusses the influence of the progressive movement in Saraiki poetry.